Introduction to "Indigenous Women: The State of Our Nations."(Canada)(Editorial) - Lawrence, Bonita; Anderson, Kim (Atlantis, 2005)
Introduction to the issue 29, 2 "Indigenous Women: The State of Our Nations".
Keywords: approches et analyses; cours; discipline; féminisme autochtone; histoire et politique; pol4105; premier cycle; sciences humaines; sciences sociales; thématiques